CLOUD APPLICATION FOR ACCOUNTING OF LIFE CYCLE OF AIRCRAFT COMPONENTS - I. G. Kirpichev; A. K. Blagorazumov; G. E. Glukhov (Научный вестник МГТУ ГА, 2017)
The paper presents a web application that facilitates accounting of life cycle of aircraft components and enables aircraft operators to transparently send data to information systems of civil aviation organizations.